Impact of insulin resistance on cardiac and vascular function. (15th October 2016) - Novo, Giuseppina; Manno, Girolamo; Russo, Rosario; Buccheri, Dario; Dell'Oglio, Sonia; Morreale, Pierluigi; Evola, Giovanna; Vitale, Giustina; Novo, Salvatore
Abstract: Background: Insulin resistance (IR), constitutes an important cardiovascular risk factor and can cause ischemic heart disease. It can lead to left ventricular dysfunction with a mechanism independent of ischemic heart disease and it is closely associated with impaired vascular function. The aim of our study was to explore the impact of IR on cardiac and vascular function, in patients with cardiovascular risk factors but angiographically undamaged coronary arteries. Methods: We studied 32 patients (62.06 ± 11.19 years) with cardiovascular risk factors. All patients underwent coronary angiography, echocardiography, Doppler ultrasound of carotid arteries and laboratory tests. Exclusion criteria were coronary artery disease detected by coronary angiography, diabetes mellitus, creatinine above 1.5 mg/dl, atrial fibrillation or malignant arrhythmias, left-ventricular hypertrophy, valvular heart disease, ejection fraction below 50%. The presence of insulin resistance was assessed using the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR). Each patient underwent a complete echocardiographic examination including Global Longitudinal Strain assessment and carotid artery ultrasound scan including measurement of arterial stiffness. Results: The patients were divided into two groups based on the median value of HOMA-IR, the first group for values < 4.14 and, the second, for values ≥ 4.14. Ejection fraction and diastolic function did not significantly differ between the two groups, whether in patients with higher levels of HOMA-IR (≥ 4.14) we observed a Global Longitudinal Strain (GLS) that was significantly reduced (− 16.50 ± 1.37% vs. − 20.73 ± 1.84%, p = 0.0015) vascular stiffness, measured in the carotid arteries as pulse wave velocity (PWV) (9.70 ± 1.75 m/s vs. 7.40 ± 1.89 m/s, p = 0.00148) that was increased. At multivariate analysis HOMA-IR was an independent predictor of myocardial dysfunction (GLS: coefficient 0.1156, p < 0.0001). Conclusion: Insulin resistance is associated with subclinical myocardial and vascular alterations in patients without significant coronary artery disease, measured as a reduction of Global Longitudinal Strain, and increased arterial stiffness. Our results underscore the importance of studying the interaction between ventricular function and vessels, in the perspective of more effective preventive and therapeutic interventions.